Incorporation of Sequence Aza‐Substitution and Thiophene Bridge in Linear Conjugated Polymers Toward Highly Efficient Photo‐Catalytic Hydrogen Evolution. Issue 11 (21st April 2022) - Chen, Ruikun; Hu, Pengwei; Xian, Yuxi; Hu, Xianhai; Zhang, Guobing
Abstract: The hydrogen evolution performance of organic photo‐catalysts is lagged by numerous factors, such as the narrow photon absorption window, low charge transport, and so on. In this paper, four linear conjugated polymers are designed and synthesized based on dibenzothiophene‐S, S‐dioxide as an acceptor, and aza‐substituted thiophene‐phenyl‐thiophene with different substitution numbers as co‐units. The polymers with the thiophene bridge and aza‐substitution exhibit broad visible absorption because of the extended conjugated length and improved planar structures resulting from the intramolecular non‐covalent interactions (S···N or CH···N). The mono‐substitution polymer without the addition of any co‐catalysts shows the highest photo‐catalytic performances with the hydrogen evolution rates of 8950 and 7388 µmol g −1 h −1 under the UV−vis (>295 nm) and visible (>420 nm) irradiation, respectively. The corresponding apparent quantum yields are as high as 8.34, 5.37, and 1.96% for the 420, 500, and 550 nm monochromatic light irradiation, respectively, which are much higher than those of the classic polymer (P7 ) without thiophene bridge and aza‐substitution. This work indicats that the incorporation of thiophene bridge enhances visible absorption and aza‐substitution optimized co‐planarity and activate reactive sites, which should be an effective strategy to improve the photo‐catalytic performance of linear conjugated polymers. Abstract : Four linear conjugated polymers with different aza‐substitution are designed and synthesized. The high hydrogen evolution rate and apparent quantum yield of mono‐substituted polymers indicate that incorporating thiophene and nitrogen atoms into the polymer backbone is an effective strategy to improve the visible photo‐catalytic performance of linear conjugated polymers.